Detection of Mycobacterium avium subsp. paratuberculosis by several diagnostics techniques in clinical suspected sheep - COELHO, A. C.; COELHO, A. M.; GARCÍA-DIEZ, J.; PIRES, M. A.; PINTO, M. L. (Journal of the Hellenic Veterinary Medical Society, 2018)
A total of thirty sheep with clinical symptomatology of paratuberculosis (Johne’s disease) were subjected to four diagnostic techniques: histopathological examination, bacteriological culture (in faeces and tissues), polymerase chain reaction (PCR) (in blood, tissue and faecal samples) and antibody responses (ELISA). Twenty-one (70.0%) animals showed histological lesions. Bacterial culture of both faeces and tissue revealed that 2 (6.7%) and 6 (20.0%) of the 30 sheep were infected, respectively. Mycobacterium avium subsp. 24 paratuberculosis (Map) was identified in 4 animals via PCR of faeces (13.3%), and in 19 (63.3%) by PCR in tissues. PCR in blood revealed 7 (23.3%) infected animals. Three (10.0%) animals showed antibodies against Map. A greater number of positive animals were detected by histopathological examination and PCR in tissues than by culture or ELISA. This study confirmed the clinical findings and results suggest that histopathology, PCR in tissues and in blood can improve the detection of Map in physically suspected animals and should be considered useful tools in the diagnosis of Map in suspected sheep.